The Effect of Profitability, KAP Reputation, Size of Audit Committee and COVID-19 Pandemic on Audit Delay (Empirical Study in Property and Real Estate Sub Sector Companies Listed on Indonesia Stock Exchange in 2016-2020) - Zumratul Meini; Selina Wulandari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to analyze the effect of profitability, Public Accounting Firm (KAP) reputation, size of audit committees and the Covid-19 pandemic on audit delay in property and real estate sub-sector companies listed on the IDX in 2016-2020. This study has a novelty by analyzing the difference in audit delay during the Covid-19 pandemic and before the Covid-19 pandemic.  The results showed that profitability negatively affects audit delay, KAP reputation has a positive effect on audit delay, Covid-19 pandemic positively affects audit delay, while size of audit committees has no effect on audit delay.  The results of this study are interesting because it is proven that covid-19 pandemic further extends the auditor's time in completing audit reports, which means the audit delay is getting longer.